ANALISIS KUALITAS WEBSITE BPOM MANOKWARI MENGGUNAKAN METODE WEBQUAL 4.0 - Ari_Fadli La Tardi; Julius Panda Putra Naibaho; Andreas Sumendap (LPPM Universitas Abdurrab, 2026)
This study is motivated by the importance of website quality in supporting digital-based public services within government institutions. The BPOM Manokwari website functions as a platform for delivering public information and services; however, its effectiveness needs to be evaluated based on user experience. The purpose of this study is to evaluate the performance of the BPOM Manokwari website by applying the WebQual 4.0 framework, which assesses website quality through three main dimensions: usability, information quality, and service interaction quality. This study employs a quantitative approach by distributing questionnaires to 112 active users of the BPOM Manokwari website. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS 4 software. This study tests hypotheses regarding the effects of usability, information quality, and service interaction quality on user satisfaction with the BPOM Manokwari website. The results indicate that only the service interaction quality dimension has a significant effect on user satisfaction, while usability and information quality do not show a significant impact. Therefore, it can be concluded that improving the quality of interactive services plays a crucial role in enhancing user satisfaction with the BPOM Manokwari website. The recommended improvements focus on navigation, content updates, and the strengthening of digital communication features. The practical implications of this study suggest that website administrators should prioritize enhancing digital communication features and service responsiveness, supported by continuous improvements in navigation and regular content updates.